Supplement to thinking in Java 2nd eddition : - Allisons, Chuck (Prentice Hall, 2000)
Introduces all the basics of objects as Java uses them; then walks carefully through the fundamentals of Java programming, including program flow, initialization and cleanup, implementation hiding, reusing classes and polymorphism